The effectiveness of Moringa oleifera as primary coagulant in high-rate settling pilot scale water treatment plant - Ng, S. C.; Saed, Katayon; Megat Mohd Noor, Megat Johari; Abdullah, Abdul Ghani Liew (Federation of Engineering Institutions of Islamic Countries, 2006)
High-rate settling module has long been found to be useful in enhancing the settling of flocs in the water treatment plant. In this study pilot plant test was carried out to assess the effectiveness of high-rate settling module for treatment of synthetic turbid water using alum. The percentage of turbidity removal using high-rate settling module was about 20% better than the turbidity removal without high-rate settling module. Furthermore, the coagulation efficiency of crushed seed kernels from Moringa oleifera Lam. was examined using high-rate settling module pilot plant. The result revealed that, seeds of M. oleifera have shown promise as a coagulant for water treatment. The turbidity after filtration was well below the World Health Organisation’s guideline value of < 5 NTU for drinking water from the synthetic turbid water of 200 NTU.